Polarization Effect on Regioselectivity of Pd‐Catalyzed Cyclization of 2‐Alkynylbenzaldehydes. Issue 2 (22nd November 2019) - Nardangeli, Nolan; Topolovčan, Nikola; Simionescu, Razvan; Hudlický, Tomáš
Abstract : We report a study on the relationship between the polarization of C≡C bond in a series of 2‐alkynylbenzaldehydes and the regioselectivity of their Pd‐catalyzed annulation reactions. The electrophilic and nucleophilic character of the triple bond carbon atoms was examined using 13 C and HMBC NMR experiments. The direction of polarization is determined only by the formyl group and its position on an aromatic ring. On the other hand, the strength of the polarization expressed through chemical shift difference Δδ of acetylenic carbon atoms is a result of electron‐withdrawing or electron‐donating ability of the other substituent. Out of two possible regioisomers, the Pd‐catalyzed cyclization reactions of 2‐alkynylbenzaldehydes that were studied predominantly afforded 1 H ‐isochromenes suggesting that the polarization of a triple bond is one of the contributing factors in the regioselectivity of this process. Abstract : The influence of C≡C bond polarization on the regioselectivity of Pd‐catalyzed cyclization of 2‐alkynylbenzaldehydes is described.